في الموسوعة النباتية للعراق Physalis angulataL.(Solanaceae)تسجيل جديد لمنوع - العلاق, سناريا عباس (Al-Nahrain Journal of Science, 2012)
Through our scientific trips to the fields, the species Physalis angulata was recorded for the first time within the flora of Iraq. The morphological characters for root, stem, leaves, flowers and fruiting parts were studied. As well as, a full description of pollen grains. Anatomical characters for epidermis of leaf, leaf venation were studied. Cross section for stems, leaves (blade and petiole) geographical distribution of the species were studied in Iraq, Results were supported with the photographs and maps.